Parents’ Education Shapes, but Does Not Originate, the Disability Representations of Their Children - Meloni, Fabio; Federici, Stefano; Dennis, John Lawrence (PLOS ONE, 2015)
The present research tested whether children’s disability representations are influenced by cultural variables (e.g., social activities, parent education, custom complex variables) or by cognitive constraints. Four questionnaires were administered to a sample of 76 primary school aged children and one of their parents (n = 152). Questionnaires included both open-ended and closed-ended questions. The open-ended questions were created to collect uncensored personal explanations of disability, whereas the closed-ended questions were designed to elicit a response of agreement for statements built on the basis of the three most widespread disability models: individual, social, and biopsychosocial. For youngest children (6–8 years old), people with disabilities are thought of as being sick. This early disability representation of children is consistent with the individual model of disability and independent from parents’ disability explanations and representations. As children grow older (9–11 years old), knowledge regarding disability increases and stereotypical beliefs about disability decrease, by tending to espouse their parents representations. The individual model remains in the background for the adults too, emerging when the respondents rely on their most immediately available mental representation of disability such as when they respond to an open-ended question. These findings support that the youngest children are not completely permeable to social representations of disability likely due to cognitive constraints. Nevertheless, as the age grows, children appear educable on perspectives of disability adhering to a model of disability representation integral with social context and parent perspective.